2022
DOI: 10.1177/01455613221144496
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Adenoid-Nasopharyngeal Ratio in the Diagnosis of Secretory Otitis Media

Abstract: Objectives To explore the associated factors of otitis media with effusion (OME) and analyze the diagnostic value of the adenoid-nasopharyngeal (A/N) ratio to OME. Methods Patients with adenoid hypertrophy (AH) recently in 2 years were collected, including sex, age, duration, with/without rhinosinusitis, and examination results, including Cone Beam Computerized Tomography (CBCT) sinus imaging, tympanometry, pure tone audiometry (PTA), blood test, and allergen detection. According to Liden/Jerger’s classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Through the ear specialist examination, it can be found that the tympanic membrane is sunken, the colour is dark or amber, bubbles or gas–liquid plane can also be seen and the tympanic activity decreases (Restuti et al., 2022). The specific manifestations of infants and young children are slow to respond to the surrounding sound, ear scratching, easy to get angry, easy to wake up from sleep and the inability to accurately turn their heads to the sound source (Li et al., 2022). Even if the child does not complain of hearing loss, parents can still find the child's behaviour changing – carelessness, lack of response to normal conversation and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Through the ear specialist examination, it can be found that the tympanic membrane is sunken, the colour is dark or amber, bubbles or gas–liquid plane can also be seen and the tympanic activity decreases (Restuti et al., 2022). The specific manifestations of infants and young children are slow to respond to the surrounding sound, ear scratching, easy to get angry, easy to wake up from sleep and the inability to accurately turn their heads to the sound source (Li et al., 2022). Even if the child does not complain of hearing loss, parents can still find the child's behaviour changing – carelessness, lack of response to normal conversation and so on.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of adenoid hypertrophy in the patients was evaluated using the Adenoid-Nasopharyngeal ratio (A/N ratio) [9] before and after treatment. The A/N ratio of ≥0.71 was used as the pathological hypertrophy standard and surgical indication.…”
Section: Degree Of Adenoid Hypertrophymentioning
confidence: 99%
“…OM is a leading cause for childhood antibiotic prescriptions, ambulatory surgery, and hearing loss 7–9 . Risk factors for AOM include those related to host (e.g., age, sex, race/ethnicity, family history of AOM and genetic predisposition, craniofacial anomalies, atopy, immunodeficiency, adenoid hypertrophy, gastroesophageal reflux) and environment (e.g., day‐care attendance, passive smoking, older siblings, use of pacifier, no breastfeeding, pollution, season) 10–14 . Research to improve OM prevention and treatment continues to be a priority given its prevalence, economic and health burdens across societies and the potential for serious difficulties including hearing loss, developmental delay, and even death 1,15,16 .…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 , 9 Risk factors for AOM include those related to host (e.g., age, sex, race/ethnicity, family history of AOM and genetic predisposition, craniofacial anomalies, atopy, immunodeficiency, adenoid hypertrophy, gastroesophageal reflux) and environment (e.g., day‐care attendance, passive smoking, older siblings, use of pacifier, no breastfeeding, pollution, season). 10 , 11 , 12 , 13 , 14 Research to improve OM prevention and treatment continues to be a priority given its prevalence, economic and health burdens across societies and the potential for serious difficulties including hearing loss, developmental delay, and even death. 1 , 15 , 16 Despite the high prevalence, morbidity, and healthcare expenditures, there remains a lack of information regarding the cellular and molecular immunologic and inflammatory events that contribute to the pathogenesis of OM.…”
Section: Introductionmentioning
confidence: 99%